Antioxidants, train longer, train harder - Hamilton, A.; Maughan, R. (Peak Performance, 2007)
Setting the Scene: Understanding antioxidants (Andrew Hamilton) Nutrition Optimum nutrition for athletes - what can we learn from recent studies? (Andrew Hamilton) Nutritional Supplements: Can antioxidants help reduce post-exercise soreness? (Andrew Hamilton) Nutritional Supplements: Antioxidant vitamins: can they do athletes more harm than good? (Andrew Hamilton) Antioxidant Protection: Antioxidant protection for athletes: is it time to ditch the pills? (Andrew Hamilton) Could ALA and ALC combine to form the Elixir of Life? (Andrew Hamilton) ALA/ALC ALA/ALC update: why the latest research is still getting scientists excited (Andrew Hamilton) Quercetin: New kid on the block - does quercetin have any value for athletes? (Ron Maughan) Magnesium: Magnesium - why it could be even more important for athletes than we thought (Andrew Hamilton)